Analogs of LDL Receptor Ligand Motifs in Dengue Envelope and Capsid Proteins as Potential Codes for Cell Entry. (3rd May 2015) - Guevara, Juan; Romo, Jaime; McWhorter, Troy; Guevara, Natalia Valentinova
Abstract : It is established that cell entry of low density lipoprotein particles (LLPs) containing Apo B100 and Apo E is mediated by receptors and GAGs. Receptor ligand motifs, XBBB XXB X, XB B XB X, and ΨB ΨXB, and mono- and bipartite NLS sequences are abundant in Apo E and Apo B100 as well as in envelope and capsid proteins of dengue viruses 1–4 (DENV1–4). Synthetic, fluorescence-labeled peptides of sequences in DENV2 envelope protein, and DENV3 capsid that include these motifs were used to conduct a qualitative assessment of cell binding and entry capacity using HeLa cells. DENV2 envelope peptide, Dsp2EP, 0564 Gly-Gly 0595, was shown to bind and remain at the cell surface. In contrast, DENV3 capsid protein peptide, Dsp3CP, 0002 Asn-Gln 0028, readily enters HeLa cells and accumulates at discrete loci in the nucleus. FITC-labeled dengue synthetic peptides colocalize with low density lipoprotein-CM-DiI and Apo E-CM-DiI to a degree suggesting that dengue viruses may utilize cell entry pathways used by LLPs.